PENGARUH MENGKONSUMSI BUAH PEPAYA (Carica papaya L.) TERHADAP KELANCARAN PRODUKSI ASI PADA IBU MENYUSUI DI KLINIK PRATAMA HANUM MEDAN TAHUN 2022 - Afrahul Padilah Siregar; Muthia Sari Mardha; Endryani Syafitri (Jurnal Maternitas Kebidanan, 2023)
According to data from the Ministry of Health, North Sumatra Province exclusive breastfeeding is still below the national average with the lowest percentage of 57.83%.. Objective: determine the effect of consuming papaya (Carica papaya I) on the smooth production of breast milk in nursing mothers at Pratama Hanum Clinic in 2022. Method; This research used a quasi-experimental method with one group pre-test post-test and was conducted at Pratama Hanum Clinic Medan. This study started from April to September 2022. The population were all nursing mothers of baby aged 0-6 months and the sample was 10 nursing mother. The data was analyzed by Wilcoxon test.. Result; The results showed that the processing of data obtained from statistical tests before and after consuming papaya fruit (Carica papaya I) obtained the Asymp.sig (2-tailed) value of .011 < .05. This means that there was an effect of consuming papaya (Carica papaya L.) on the smooth production of breast milk in nursing mothers. Conclusion; The conclusion in this study shows that after consuming papaya the average value obtained is 51.00 and there is a difference in the pretest and posttest, which is 28.4 which means that there is an effect of consuming papaya (Carica papaya L.) on the smooth production of breast milk in nursing mothers